2019
DOI: 10.1038/s41598-018-36688-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Sublethal External Exposure to Deep Water Horizon Oil on the Avian Metabolome

Abstract: We assessed adverse effects of external sublethal exposure of Deepwater Horizon, Mississippi Canyon 252 oil on plasma and liver metabolome profiles of the double-crested cormorant (Phalacrocorax auritus), a large (1.5 to 3.0 kg) diving waterbird common in the Gulf of Mexico. Metabolomics analysis of avian plasma showed significant negative effects on avian metabolic profiles, in some cases after only two external exposures (26 g cumulative) to oil. We observed significant (p < 0.05) changes in intermediate met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Multiple metabolic pathways associated with energy production were impaired in doublecrested cormorants dermally exposed to oil such that 20% of their surface area was lightly oiled (Dorr et al 2019). Both plasma and liver metabolomes were affected compared to controls indicating potential impacts to thermoregulation, cardiac function, and hematologic parameters.…”
Section: Fishmentioning
confidence: 97%
“…Multiple metabolic pathways associated with energy production were impaired in doublecrested cormorants dermally exposed to oil such that 20% of their surface area was lightly oiled (Dorr et al 2019). Both plasma and liver metabolomes were affected compared to controls indicating potential impacts to thermoregulation, cardiac function, and hematologic parameters.…”
Section: Fishmentioning
confidence: 97%
“…Dorr et al (2019) assessed the adverse effects of repeated, sublethal, external exposure of artificially weathered Deepwater Horizon (DWH) crude oil on metabolites extracted from the plasma and liver of Phalacrocorax auritus (Double‐crested Cormorants). 6.5 g of oil was applied to the backs and breasts (13 g total) of birds every 3 days throughout the 15‐day exposure period.…”
Section: Laboratory Studies On Effects Of Crude Oilsmentioning
confidence: 99%
“…In contrast, metabolomics studies have rarely been applied to the field of avian ecotoxicology, and have only focused on one of two species: chicken or double-crested cormorant [ 5 , 6 , 7 , 8 , 9 , 10 ]. These studies revealed that lipid metabolism was affected by exposure to perfluorooctanesulfonic acid, chromium, and alpha-cypermethrin in chickens [ 6 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%